(untitled) (Archives of Criminology, 2023)
In the recent penological literature, the back door of a prison is often presented as a revolving door through which many prisoners leave the prison prematurely, but then return after a short period. A large number of prisoners who have been conditionally released are sent back to prison during the licence period or before the end of their sentence due to a breach of the licence conditions. Since the revocation of a release modality (such as parole) might affect reintegration, a careful balance is needed between proportionality, the risks, the possibility of behavioural change and the opportunities for reintegration. In other words, the impact on detainees should not be underestimated if a decision to recall is being taken. Since the majority of parolees in Belgium are sent back to prison after non-compliance with the imposed conditions, this article discusses the experiences of interviewees who lived under these conditions when being granted a release modality before being recalled to prison.